Challenges in Enforcing Laws Against Cybercrime in the National Criminal Justice System - Yandi Wahyudi; Rahadian, Dian; Awaludin, Arif (Jurnal Ar Ro'is Mandalika (Armada), 2025)
The exponential rise of cybercrime has presented profound challenges to national criminal justice systems worldwide. This article aims to analyze the key obstacles faced by national authorities in enforcing cybercrime laws, particularly in the context of outdated legal frameworks, technological limitations, and operational inefficiencies. Using a qualitative approach through library research and literature review methods, this study synthesizes findings from scholarly sources, international reports, and comparative legal analyses to provide a comprehensive understanding of the enforcement gaps and institutional weaknesses in responding to cyber threats. The results reveal that many national legal systems lack harmonized legislation aligned with international frameworks, making cross-border prosecution complex and inconsistent. Technological barriers such as the widespread use of encryption, limited digital forensic capacities, and the increasing sophistication of cybercriminal methods further complicate enforcement efforts. In addition, operational challenges—including insufficient training, poor interagency coordination, and lack of resources—significantly impede law enforcement effectiveness. This article argues for the urgent modernization of legal structures, the investment in forensic and technological infrastructure, and the enhancement of international cooperation mechanisms. It concludes by proposing strategic, systemic reforms to bridge enforcement gaps and offers recommendations for future research on best practices, technology integration, and legal harmonization in cybercrime law enforcement. This study contributes to the scholarly discourse by highlighting the critical intersection between law, technology, and governance in the digital era.